2016
DOI: 10.1016/j.biopsych.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Plasticity in Accumbens Core Contributes to Incubation of Methamphetamine Craving

Abstract: BACKGROUND The incubation of cue-induced drug craving in rodents provides a model of persistent vulnerability to craving and relapse in human addicts. After prolonged withdrawal, incubated cocaine craving depends on strengthening of nucleus accumbens (NAc) core synapses through incorporation of Ca2+-permeable AMPA receptors (CP-AMPARs). Through mGlu1-mediated synaptic depression, mGlu1 positive allosteric modulators (PAMs) remove CP-AMPARs from these synapses and thereby reduce cocaine craving. This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 70 publications
10
109
0
Order By: Relevance
“…Left, MeanϮ SEM ␤-gal-positiveneuronsintheOFCinthefourgroups.Right,Representativephotomicrographsof␤-galexpressionintheOFCofratsinthedifferenttreatmentgroups.WeinjectedtheratswithDaun02orvehicle 75 min after a short 15 min extinction session in the nicotine self-administration context or exposure to a novel context on withdrawal day 11. n ϭ 6 -8 per group. methamphetamine (Li et al, 2015b), and cocaine (Lu et al, 2009) craving are observed at this withdrawal time period, as well as after longer withdrawal periods (Lu et al, 2004a;Venniro et al, 2016;Wolf, 2016). These time course differences may reflect drug-specific differences in the duration of incubation of craving (Pickens et al, 2011), but may also reflect the use of a limitedaccess training procedure in our study.…”
Section: Nicotine Self-administration and Incubation Of Nicotine Cravmentioning
confidence: 54%
See 3 more Smart Citations
“…Left, MeanϮ SEM ␤-gal-positiveneuronsintheOFCinthefourgroups.Right,Representativephotomicrographsof␤-galexpressionintheOFCofratsinthedifferenttreatmentgroups.WeinjectedtheratswithDaun02orvehicle 75 min after a short 15 min extinction session in the nicotine self-administration context or exposure to a novel context on withdrawal day 11. n ϭ 6 -8 per group. methamphetamine (Li et al, 2015b), and cocaine (Lu et al, 2009) craving are observed at this withdrawal time period, as well as after longer withdrawal periods (Lu et al, 2004a;Venniro et al, 2016;Wolf, 2016). These time course differences may reflect drug-specific differences in the duration of incubation of craving (Pickens et al, 2011), but may also reflect the use of a limitedaccess training procedure in our study.…”
Section: Nicotine Self-administration and Incubation Of Nicotine Cravmentioning
confidence: 54%
“…We used an extinction-based experimental procedure (Pickens et al, 2011;Wolf, 2016) to study time-dependent increases in nicotine seeking after withdrawal (incubation of nicotine craving) after adolescent-and adult-onset drug self-administration in rats. We report four main findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the lack of sex differences in incubation of methamphetamine craving after forced abstinence were not predicted based on a comprehensive study of Kerstetter et al (2008) showing sex differences in incubation of cocaine craving. An important consideration regarding these discrepant results is that recent evidence indicates mechanistic differences in incubation of cocaine versus methamphetamine craving (Li et al, 2015;Scheyer et al, 2016). Thus, sex differences in brain function that impact mechanisms of …”
Section: Incubation Of Methamphetamine Craving After Voluntary or Formentioning
confidence: 96%